Validation techniques II: discriminatory power and calibration - Tasche, Dirk (Henry Stewart Talks, 2007)
Validation principles, Predictive ability, discriminatory power and PD calibration, Cumulative accuracy profile (CAP), Accuracy ratio (AR), Receiver operating characteristic, Kolmogorov-Smirnov statistic, Conditional and unconditional tests, Binomial test, Hosmer-Lemeshow test, Spiegelhalter test, Normal test
Archived at 2022/04/04